A guarda compartilhada como forma de cogestão parental : avanços, desafios e contradições - Rosa, Conrado Paulino da (2017)
The present thesis addresses, in an interdisciplinary way, the management of the life of the children after the dissolution of a marriage or a common-law marriage. The research begins with the analysis of the advance of the legislation pertinent to the thematic having in view that originally in our legal system there was only the prediction of the unilateral custody that, because of social issues, ended up being determined only in favor of the mother. With the attribution, the ascendant custodial parent exclusively decides on all matters pertaining to the life of the offspring. However, in 2008, Law 11,698 amended articles 1,583 and 1,584 of the Civil Code to establish the possibility of shared custody between parents, which is “joint responsibility and the exercise of the rights and duties of the father and the mother who do not live under the same roof, concerning the family power of common children”. Nevertheless, since then, it has been usual the social confusion of the institute of the sharing with of the partial custody, which would represent a static division of time between both parents, in which the parent in his company would have exclusive decision-making power. Considering that there was never the possibility of partial custody in Brazil, in 2014 there was a need for a new amendment modifying the Civil Code through Law 13,058. Among the changes, the application of shared custody became the preferential route and the unilateral, as a consequence, the restrictive way. In addition, it was clarified that the sharing can be applied even when parents reside in different cities and also when there is litigation between them. Another fact to be considered is the constant presence of processes where there is parental alienation between the parents. According to Law 12,318/2010, it is considered an act of parental alienation the interference in the psychological formation of the child or adolescent promoted or inducted by one of the parents, by the grandparents or by those who have the child or adolescent under their authority, custody or supervision to repudiate or to cause damage to the establishment or maintenance of bonds with the parent. In this vein lies the problem of this thesis: in which way does joint custody represent some kind of change in coparenting? Through the analysis of content, using the documentary analysis as a research procedure and, as a corpus of analysis the legislation on the subject, which are Federal Constitutions, Civil Code of 1916 (Law 3,071/1916), Married Woman Statute (Law 4,121/1962), Constitutional Amendment n. 9/1977, Child and Adolescent Statute (Law 8,069/1990), Civil Code of 2002 (Law 10,406), Law 11,698/2008, Law 12,318/2010, Law 13,058/2014 and Code of Civil Procedure of 2015 (Law 13,105). Moreover, this thesis will be based on bibliographies, not only from Social Service, but also from Psychology and Law. It will seek to verify the viability of the coactive shared custody as a hindering means of the practice of parental alienation and also as a way of effectuation of the rights of children and adolescents.